2023
DOI: 10.1128/spectrum.00700-23
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Classic, MLB, and VA Astroviruses in Children with Acute Gastroenteritis, 2014–2021: Emergence of MLB3 Strain in Japan

Abstract: HAstVs are one of the pathogens of viral AGE and are considered the third most common viral agents of AGE after rotavirus and norovirus. HAstVs are also suspected to be the causative agents of encephalitis or meningitis in immunocompromised patients and elderly persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…In other works, it was found that human astrovirus causes 10% of acute gastroenteritis sporadic cases in children of <3 y, and that most outbreaks occurred mainly in healthcare and daycare centers, while in some developing countries, infection rates reached 20% [117]. The symptoms of gastrointestinal tract and inflammatory lesions affecting the meninges and brain tissue as encephalitis and meningitis were also reported [122,123]. The general and clinical characteristics of astrovirus are presented in Table 1.…”
Section: Astrovirusmentioning
confidence: 95%
“…In other works, it was found that human astrovirus causes 10% of acute gastroenteritis sporadic cases in children of <3 y, and that most outbreaks occurred mainly in healthcare and daycare centers, while in some developing countries, infection rates reached 20% [117]. The symptoms of gastrointestinal tract and inflammatory lesions affecting the meninges and brain tissue as encephalitis and meningitis were also reported [122,123]. The general and clinical characteristics of astrovirus are presented in Table 1.…”
Section: Astrovirusmentioning
confidence: 95%